EDP Baixo Sabor: Construction and Reservoir Filling Phases - Iberian Wolf [howling surveys] - [2010-2014] ... - Mota, Paulo; Vingada, José Vítor; Ferreira, Joana; Diogo, Hugo Manuel; Morgado, Rui Guilherme; Rodrigues, Pedro; Garrido, Nuno; Eira, Catarina Isabel; Pinto, Nuno; Marques, Carina (EDP - Energias de Portugal, 2020)
The dataset contains the results of Iberian Wolf (Canis lupus) (Mammalia) surveys made in the lower valley of River Sabor (NE Portugal), some of its small tributaries, and in the rivers Maçãs and Angueira, in the scope of the long-term Ecological Monitoring Program (PME) of the Baixo Sabor Hydroelectric Dams (AHBS), promoted by EDP – Energias de Portugal, S.A. Surveys were made in the area affected by the dam, and in control areas farther from the dam, from June 2010 to August 2014. Sampling was performed 1-3 times a year, between May and November, with a total of 19-28 howling stations sampled each year. No detection of Iberian wolf was obtained during these surveys, thus the dataset reports on locations where the species was deemed absent, thereby providing a baseline to assess future changes in species occurrence patterns. ...